Detecting Earnings Management. - Dechow, Patricia M.; Sloan, Richard G. (The Accounting Review, 1995)
Evaluates alternative accrual-based models for detecting earnings management. Comparison of the specification and power of commonly used test statistics; Application of the models to a random sample of firm-years; Importance of controlling for financial performance when investigating earnings management stimuli that are correlated with financial performance.